2017
DOI: 10.1111/jocn.13870
|View full text |Cite
|
Sign up to set email alerts
|

The quality of life of people who have chronic wounds and who self‐treat

Abstract: Aims and objectives: The aim of this study was to investigate the effect of chronic wounds on the physical, emotional, social, lifestyle and financial domains of quality of life among people who self-treat their wounds.Background: Patient-centred models of care have received increased attention over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
101
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 33 publications
0
101
0
23
Order By: Relevance
“…Skin trauma will destroy the barrier function of the skin, weaken normal functions and even induce skin tumors . Although most skin traumas are self‐healing, promoting the closure of skin wound by pharmacological means is beneficial to shortening the course of the wound, reducing the risk of systemic infection and satisfying the cosmetic needs of the patients . Therefore, it is one of the hot topics in clinical research to seek candidate agents or methods to promote skin wound healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin trauma will destroy the barrier function of the skin, weaken normal functions and even induce skin tumors . Although most skin traumas are self‐healing, promoting the closure of skin wound by pharmacological means is beneficial to shortening the course of the wound, reducing the risk of systemic infection and satisfying the cosmetic needs of the patients . Therefore, it is one of the hot topics in clinical research to seek candidate agents or methods to promote skin wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…beneficial to shortening the course of the wound, reducing the risk of systemic infection and satisfying the cosmetic needs of the patients. [4] Therefore, it is one of the hot topics in clinical research to seek candidate agents or methods to promote skin wound healing.…”
mentioning
confidence: 99%
“…The psychosocial effects of chronic wounds include emotional distress because of pain and withdrawal from social and work activities, and must be considered within a holistic patient assessment (Pragnell andNeilson 2010, Dowsett andvon Hallern 2017). Kapp et al's (2018) study of 25 adult patients with chronic wounds found that they all experienced adverse psychosocial effects, such as an inability to exercise or socialise as they had previously, disrupted employment and increased financial pressures resulting from wound dressing and care costs. Other studies have detailed the emotional implications of chronic wounds, particularly where wound pain and pain during dressing changes negatively affected patients' psychological well-being (Pragnell andNeilson 2010, Upton et al 2012).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Other studies have detailed the emotional implications of chronic wounds, particularly where wound pain and pain during dressing changes negatively affected patients' psychological well-being (Pragnell andNeilson 2010, Upton et al 2012). Kapp et al (2018) also identified that patients with chronic wounds could become frustrated and distrustful of healthcare staff because of the complexity and variation in their opinions regarding effective treatments. As a result of these factors, nurses may encounter an understandable reluctance on the part of patients with chronic wounds to continue with | PEER-REVIEWED | skin care / evidence & practice treatment (Upton et al 2012, Kapp et al 2018.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Chronic wound is de ned as a wound that has failed to achieve anatomical and functional integrity through orderly and timely repair within 3 months (17), and is prevalent in the population with the number of patients increasing year by year (18)(19)(20). Besides similar to the COVID-19, the middle-aged population and diabetics are at high risk of chronic wounds (11,18,21). Although wound non-healing is considered multifactorial in nature (17), infection and microbial implantation may be the single most likely and unavoidable cause of delayed wound healing (22,23), and without timely and effective treatment, bacterial implantation in the body can lead to systemic infection or even life-threatening infection (24,25).…”
Section: Introductionmentioning
confidence: 99%